Filarial Lymphedema Patients Are Characterized by Exhausted CD4+ T Cells - Sacha Horn; Manuel Ritter; Kathrin Arndts; Dennis Borrero-Wolff; Anna Wiszniewsky; Linda Batsa Debrah; Linda Batsa Debrah; Linda Batsa Debrah; Alexander Y. Debrah; Alexander Y. Debrah; Alexander Y. Debrah; Jubin Osei-Mensah; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Worldwide, more than 200 million people are infected with filariae which can cause severe symptoms leading to reduced quality of life and contribute to disability-adjusted life years (DALYs). In particular, lymphatic filariasis (LF) caused by Wuchereria bancrofti can lead to lymphedema (LE) and consequently presents a serious health problem. To understand why only a fraction of the infected individuals develop pathology, it is essential to understand how filariae regulate host immunity. The central role of T cells for immunity against filariae has been shown in several studies. However, there is little knowledge about T cell exhaustion, which causes T cell dysfunction and impaired immune responses, in this group of individuals. Recently, we showed that LE patients from Ghana harbor distinct patterns of exhausted effector and memory CD8+ T cell subsets. Based on these findings, we now characterized CD4+ T cell subsets from the same Ghanaian patient cohort by analyzing distinct markers within a 13-colour flow cytometry panel. We revealed that LE patients had increased frequencies of CD4+ T cells expressing exhaustion-associated receptors such as KLRG-1, TIM-3 and PD-1 compared to healthy endemic normal and W. bancrofti-infected individuals. Moreover, CD4+ T cells in LE patients were characterized by distinct co-expression patterns of inhibitory receptors. Collectively with the previous findings on CD8+ T cell exhaustion patterns, the data shown here demonstrates that filarial LE patients harbor distinct subsets of exhausted T cells. Thus, T cell exhaustion patterns in LE patients need attention especially in regards to susceptibility of concomitant infections and should be taken into consideration for LE management measures.